Seismic fragility analysis of adjacent inelastic structures connected with viscous fluid dampers. Issue 1 (January 2017) - Wu, Qiao-Yun; Zhu, Hong-Ping; Chen, Xu-Yong
Many scholars have conducted vibration control analysis on adjacent structures, so far. However, most of the previous studies always focus on the elastic analysis of the structures which usually can't meet the multi-level seismic targets of structural safety and using function, and often ignore the adverse effects of near-field earthquakes. In view of the limitations of elastic vibration control analysis, two-dimensional models of some adjacent inelastic reinforced concrete frame structures which are connected with the viscous fluid dampers (modeled by Maxwell model) were set up, and incremental dynamic analysis was conducted under 20 near-field and 20 far-field seismic waves to get the entire seismic response process. The seismic fragility curves of the adjacent structures which were controlled and uncontrolled were obtained. The applicability of the Maxwell damper optimum parameter expressions under different seismic performance levels was studied and the differences of seismic response of the adjacent structures under the far-field and near-field earthquakes were compared. Finally, through a large number of parametric analysis and based on the principle of minimum seismic fragility of the adjacent structures, the appropriate damping values of the Maxwell dampers which show preferable control effects under different seismic waves and seismic intensities were proposed.